1991
DOI: 10.1007/bf01403003
|View full text |Cite
|
Sign up to set email alerts
|

Acetazolamide reactivity on cerebral blood flow in patients with subarachnoid haemorrhage

Abstract: Cerebral vasodilatory capacity was evaluated by acetazolamide-activated N-isopropyl-p-[123I]iodoamphetamine (123I-IMP) single photon emission computed tomography (SPECT) in 42 patients with subarachnoid haemorrhage (SAH). A low perfusion area was present in the corresponding region of haematoma seen on the CT and continued to be noted throughout the time courses. Deteriorated acetazolamide reactivity affected by surgical intervention was seen in 100% of the patients who underwent aneurysm repair in the 1st pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…1,2,11,16) This weak autoregulatory response has been attributed to maximal dilation of the peripheral arterioles to maintain sufficient cerebral blood flow in the presence of decreased cerebral perfusion pressure due to vasospasm. However, a recent histological study revealed that intraparenchymal small arteries or arterioles show luminal narrowing rather than dilation during cerebral vasospasm after experimental SAH.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,11,16) This weak autoregulatory response has been attributed to maximal dilation of the peripheral arterioles to maintain sufficient cerebral blood flow in the presence of decreased cerebral perfusion pressure due to vasospasm. However, a recent histological study revealed that intraparenchymal small arteries or arterioles show luminal narrowing rather than dilation during cerebral vasospasm after experimental SAH.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that cerebral vasospasm of large arteries is accompanied by a massive dilation of the intraparenchymal vessels [28]. A CBF study using single photon emission computed tomography showed that CBF did not increase by administering acetazolamide in SAH patients [29]. Furthermore, a transcranial Doppler sonography (TCD) study revealed that hypercapnia does not decrease flow velocities in the middle cerebral arteries or the internal carotid arteries of patients with cerebral vasospasm [30].…”
Section: Previous Concepts Regarding DCI Pathogenesismentioning
confidence: 99%
“…Furthermore, a transcranial Doppler sonography (TCD) study revealed that hypercapnia does not decrease flow velocities in the middle cerebral arteries or the internal carotid arteries of patients with cerebral vasospasm [30]. These decreased reactivities to vasodilating stimuli were thought to be due to a lack of response by small vessels because of their maximal dilation in an attempt to maintain sufficient CBF in the face of severe vasospasm [29, 30]. Studies using several imaging techniques in patients with SAH [3134] and in animal models of SAH [3537] have suggested the existence of microvessel constriction and microthrombi formation after SAH.…”
Section: Previous Concepts Regarding DCI Pathogenesismentioning
confidence: 99%
“…Therefore, AZ tests may help in timing surgery and in the follow‐up of patients after the operation (Mourier et al. , 1991; Shinoda et al. , 1991; George et al.…”
Section: Vasospasm After Aneurysmal Subarachnoid Hemorrhagementioning
confidence: 99%